Discussion on Main Influencing Factor of Wear Resistance of Pre-lubricating Roller Chain - Zhaohua Shang; Wenjun Tao; Chengfeng Liu; Hongju Fu; Anlong Zhang (Jixie chuandong)
The lubrication state has a great influence on the wear resistance of the ordinary industrial roller chain. The main factors affecting the wear resistance of the ordinary pre-lubricating roller chain are summarized starting with the movement characteristics，wear principle and lubrication condition of the roller chain，combining with the wear resistance bench test，customer feedback and personal experience of the chain，and concludes that the meshing impact，vibration，force condition and rotation speed of the chain will affect the storage of grease in the chain，thus affecting the wear resistance of the chain，while the machining precision，surface state and heat treatment process of the chain parts will also affect the wear resistance of the chain.